The Students and Teacher’s Perception of Mobile-Assisted Language Learning Integration in EFL Teaching-Learning Practices - Fuady, Farhan; Sadikin, Irma Savitri (Linguistics and ELT Journal, 2023)
In the ever-evolving landscape of language education, technology propelled people toward new horizons, acting as the wind in their sails. Mobile-Assisted Language Learning (MALL) stood at the helm of this digital voyage, reshaping how people acquired languages. When setting these targets, the researcher focused on considering the quality requirements of mobile applications, taking into account the perspectives of both users and instructors. Therefore, the study aimed to analyze students' and teachers' perceptions of MALL integration in teaching-learning practice. For this study, the researcher chose a descriptive qualitative approach. The researcher used a questionnaire and an interview to collect both quantitative and qualitative data perspectives. The researcher quantitatively presented the percentage data of the questionnaire, and qualitatively, an analysis of interview responses was conducted, obtained from three classes and a teacher from one of the Private Junior High Schools in Jakarta. In a quantitative data perspective, students demonstrated favorable ratings on measures of usefulness, ease of use, and satisfaction when utilizing MALL (Mobile-Assisted Language Learning) in their English classrooms, as indicated by responses collected through Google Forms. From a qualitative perspective, both teachers and students concurred that MALL held the potential for enhancing both soft and hard skills. It fostered learning focus and independent study, offered convenience through its availability anytime and anywhere, optimized battery and data consumption, and facilitated communication between students and teachers. The result was an expressed desire to utilize MALL in the future.